EFFECT OF INCISOR POSITION AND INCLINATION ON SMILING PROFILE ATTRACTIVENESS - Charoenpong, Hataichanok; Kittisathakul, Auksorn; Engkatanachai, Kulapatch; Patimaarak, Chachavudh; Chanchaichujit, Glit; Chotesmithkul, Cheerana; Sunthonkitjarak, Weerawat; Boonlee, Pusaji; Akkaraitthiphong, Phimnaphat (Interprofessional Journal of Health Sciences, 2023)
Incisor position and inclination not only affect tooth function but also affect facial attractiveness which is the major concern of patient seeking orthodontic treatment nowadays. This study aimed to evaluate facial attractiveness in smiling profile view with different incisor position and inclination in Thai people. The photograph in smiling profile view of chosen Thai model was modified using Photoshop to obtain 8 additional photos with 2 different positions (-3 and +3 mm) and 2 different inclinations (-6 and +6 degree). Therefore, the total of 9 images was created. The 402 Thai subjects were asked to evaluate attractiveness of each image using visual analog scale.The results showed that normal position and 3 mm retrusion received higher attractiveness score than 3 mm protrustion. Normal inclination or +6 degree proclination received higher score than retroclination. The results showed that normal position and 3 mm retrusion received higher attractiveness score than 3 mm protrusion. Normal inclination or +6 degree proclination received higher score than retroclination. When considering position together with inclination, the results showed that either protrusive or retrusive incisor position, normal inclination had significantly higher attractiveness score compare to proclination or retroclination. These results suggested that protrusion of upper incisors in Thai caused reduction in facial attractiveness. Normal inclination or slightly proclined upper incisor had better attractiveness compared to retroclined upper incisors. When incisor position is changed into more protrusive or retrusive position, the inclination should be kept normal in order to maximize facial attractiveness.